Hereditary Haemorrhagic Teleangiectasia: Diagnostic Imaging of Visceral Involvement - Memeo, Maurizio; Scardapane, Arnaldo; Ianora, Amato A.S.; Sabba, Carlo; Angelelli, Giuseppe (Current Pharmaceutical Design, 2006)
Hereditary Haemorrhagic Telangiectasia (HHT), also known as Rendu-Osler-Weber disease, is an autosomaldominant vascular disease characterised by mucocutaneous or visceral angiodysplastic lesions (telangiectases and arteriovenous malformations), which may be widely distributed throughout the cardiovascular system. Its diagnosis is based on clinical criteria. Liver, lungs and brain, in order of prevalence, are the most frequently involved visceral districts of the body other than skin and nasal mucosa. Liver involvement is frequent and characterised by the presence of intrahepatic shunts, disseminated intraparenchymal telangiectases and other vascular lesions. Although it is usually asymptomatic, congestive cardiac failure, portal hypertension, portosystemic encephalopathy, cholangitis or atypical cirrhosis are possible complications. Pulmonary arteriovenous malformations involve more than one third of HHT patients and can consist of diffuse telangiectases or high-flow low-pressure shunts between pulmonary arteries and veins. Pulmonary involvement can cause serious complications: hypoxaemia, pulmonary or pleural hemorrhage, paradoxical embolism into cerebral circulation. Various types of cerebrovascular malformations can affect HHT patients and the most common are arteriovenous malformations, consisting of one or more feeding arteries connected to one or more draining veins. Diagnostic imaging has a fundamental role in detecting the alterations involving these various districts in the body. The possibility to perform fast and complete studies and to provide high quality multiplanar and angiographic reconstructions, gives multi-detector row helical computed tomography and magnetic resonance the ability to detect and characterise the complex anatomopathological alterations typical of HHT. Ultrasonography seems to be the best screening modality for hepatic and pulmonary involvement.
Keywords: pulmonary arteriovenous malformations